DETECTION OF MUTATIONS IN THE KatG GENE RELATED TO ISONIAZID RESISTANCE OF MYCOBACTERIUM TUBERCULOSIS COLLECTED IN CENTRAL AND SOUTH VIETNAM - Ngoc, Nghiem Minh; Hoai Thu, Nguyen Thi (Vietnam Journal of Biotechnology, 2018)
Infection of Mycobacterium tuberculosis (MTB) is one of the most common infections in humans. However, the detection rate is only 37% of estimated patients. Currently, Tuberculosic bacteria (TB) are becoming more serious with many TB strains developing multi-drug resistance, and particularly, in case of co-infection with TB and HIV/AIDS. The izoniazid resistant TB strains (INH) also resistant to the other anti-TB antibiotics. The molecular biology methods have allowed rapid and accurate diagnosis of patients infected with drug-resistant TB bacteria. In this study, we used primers katG-F and katG-R designed for amplication of a fragment of 684 bp in katG gene in 7 strains of TB bacteria collected in Pham Ngoc Thach - Ho Chi Minh city and Hue Central hospitals. Sequence analysis of the katG gene fragments showed that 5 samples had substitution mutations at codon 315 (point mutation G to C), leading to the change of amino acid from Serine to Threonine (S315T). In the 5th sample there appeared another mutation at codon 324, changing amino acid Aspartic (D) to Glycine (G) (D324G). In the sample DA1, no mutation has been found in any codon in the katG gene fragment studied. The results obtained in this study may have important implications in changing the treatment regimen and control of tuberculosis in a country with high number of TB patients as in Vietnam